Peroxide cross-linked polyethylene insulating material for 500kV ultrahigh-voltage direct-current cable and preparation method thereof
By using hindered phenol antioxidant to modify the combination of silica and thiosilane coupling agent in polyethylene insulating materials, the problem of space charge accumulation in DC cables is solved, and the DC breakdown strength and material stability are significantly improved , ensuring the safe and stable operation of the power grid.
Patent Information
- Application Number
- CN202411325183.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-17
AI Technical Summary
The prior art is difficult to effectively suppress the accumulation of space charge in 500kV ultra-high voltage DC cable insulating materials, and the nano-doping technology has agglomeration problem and long-term stability, which affects the safe and stable operation of the power grid.
The modified silica is combined with the thio silane coupling agent by using hindered phenol antioxidant, and the nanosilica is modified by photo-induced reaction, which significantly improves the DC breakdown strength and dispersion of the polyethylene insulating material and inhibits space charge aggregation.
It significantly improves the DC breakdown strength and comprehensive performance of polyethylene insulating materials, extends the service life of the cable, and ensures the safe and stable operation of the power grid.
Smart Images

Figure QLYQS_1 
Figure BDA0005055221250000031 
Figure BDA0005055221250000032
Abstract
Description
Technical Field
[0001] The invention belongs to the field of insulating material preparation, and in particular relates to a peroxide cross-linked polyethylene insulating material for a 500kV ultra-high voltage direct current cable and a preparation method thereof. Background Art
[0002] Polyethylene (PE) is a material with good performance that has been widely used in recent years. Due to its simple manufacturing process and excellent mechanical, electrical and thermal properties, it has become a common raw material for making cable insulation materials and is widely used in power transmission and distribution network systems. However, due to the phenomenon of electrical aging during the power distribution process, the service life of cable insulation materials made of polyethylene in actual life is often lower than the theoretical life. It can be seen that how to improve the electrical resistance of polyethylene cable insulation materials and improve their reliability and service life is very important to ensure the safe and stable operation of the power grid.
[0003] Patent CN 110791003 A discloses an anti-water tree cable insulation material, the components of which include low-density polyethylene, diisopropylbenzene peroxide and a graftable antioxidant; the graftable antioxidant has an olefin-unsaturated substituent, an aromatic amine / hindered phenol antioxidant group and a hydrophilic polar group. The invention adds a graftable antioxidant containing a hydrophilic polar group to low-density polyethylene, initiates it with a free radical initiator, and melt grafts while cross-linking occurs, grafting and fixing the antioxidant on the cross-linked polyethylene macromolecular chain, reducing the precipitation of the antioxidant, improving the heat aging resistance of the insulation material, and inhibiting the initiation and growth of water tree branches in the insulation. However, the insulation material in the invention belongs to AC power cable insulation material, which is not suitable for use with DC power, and its comprehensive performance still needs to be improved.
[0004] For cross-linked polyethylene insulation materials used in high-voltage DC cables, how to suppress the space charge problem has become a technical challenge in the development of DC cables. The existing technology uses nano-doping technology to suppress the generation and accumulation of space charge, which has attracted widespread attention. However, nanoparticles are very easy to agglomerate, and the addition of agglomerated powders will bring new impurities into the insulation material. In addition, the long-term stable production and processing of nano-modified insulation systems is also an important factor restricting its development.
[0005] In view of the deficiencies in the existing technology, a DC cable insulation material with space charge suppression effect and good comprehensive performance is developed, which can effectively control the accumulation of space charge under a DC field, which is of great significance for ensuring the safe and stable operation of the power grid. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a peroxide cross-linked polyethylene insulation material for a 500kV ultra-high voltage DC cable and a preparation method thereof. The prepared cross-linked polyethylene cable insulation material has excellent performance, wherein the synthesized hindered phenol antioxidant modified silica improves the DC breakdown strength of the polyethylene insulation material and has a significant effect in inhibiting space charge accumulation.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The first aspect of the present invention provides a method for preparing a peroxide cross-linked polyethylene insulation material for a 500 kV ultra-high voltage DC cable, comprising the following preparation steps:
[0009] The low-density polyethylene base material is added into a reciprocating mixer for preliminary melting, the hindered phenol antioxidant modified silica is added for uniform mixing, and finally dicumyl peroxide is added for heat preservation and absorption at 70-110°C for 10-12h to obtain peroxide cross-linked polyethylene insulation material.
[0010] In some embodiments, the amount of the hindered phenol antioxidant modified silica is 0.5-2.5 wt‰ of the low density polyethylene base material.
[0011] Preferably, the amount of the hindered phenol antioxidant modified silica is 1.5wt‰ of the low density polyethylene base material.
[0012] In some embodiments, the preparation steps of the hindered phenol antioxidant modified silica are:
[0013] S1: putting nano-silica into anhydrous ethanol, adding mercaptosilane coupling agent thereto, and after ultrasonic dispersion, reacting in a closed environment at 110-120° C. for 4-6 hours, washing, vacuum drying and grinding to obtain modified silica;
[0014] S2: In a nitrogen atmosphere, the modified silica of step (1) is mixed with a hindered phenol antioxidant, a photoinitiator TPO, and dichloromethane, and reacted with ultraviolet light for 1-2 hours at 0-4° C. with stirring, and then vacuumed to obtain hindered phenol antioxidant modified silica.
[0015] The amount of the photoinitiator TPO used is 0.5-2wt% of the hindered phenol antioxidant.
[0016] The present invention firstly modifies nano silicon dioxide with a certain particle size by controlling the raw material ratio and using a mercaptosilane coupling agent and a hindered phenol antioxidant, and then applies the modified nano silicon dioxide to a polyethylene insulating material, which can significantly improve its comprehensive performance. This is because the mercaptosilane coupling agent first self-polymerizes on the surface of the nano silicon dioxide, introduces a large number of mercapto groups on the surface of the nano silicon dioxide, and under the action of a photoinitiator TPO, the sulfur groups on the nano silicon dioxide react chemically with the vinyl groups in the hindered phenol antioxidant, and one side of the double bond can generate free radical polymerization, while the other side of the double bond has a large steric hindrance, which can effectively reduce the possibility of free radical polymerization, thereby improving the dispersibility of the nano silicon dioxide, making it less likely to agglomerate, having a stronger nucleation ability, and being conducive to improving the dielectric properties of the polyethylene material, especially the DC breakdown strength.
[0017] In some embodiments, the average particle size of the nano-silica is 50-100 nm.
[0018] In some embodiments, the amount of the mercaptosilane coupling agent is 2-6 wt % of the nano-silica; the mercaptosilane coupling agent is γ-mercaptopropyltrimethoxysilane or γ-mercaptopropyltriethoxysilane.
[0019] Preferably, the amount of the mercaptosilane coupling agent is 3.5 wt % of the nano-silicon dioxide.
[0020] In some embodiments, the mass ratio of the modified silica to the hindered phenol antioxidant is (1-10):1.
[0021] Preferably, the mass ratio of the modified silica to the hindered phenol antioxidant is (4-8):1.
[0022] Further preferably, the mass ratio of the modified silica to the hindered phenol antioxidant is 6.5:1.
[0023] In some embodiments, the hindered phenol antioxidant has the structural formula:
[0024]
[0025] Preferably, the synthesis steps of the hindered phenol antioxidant are:
[0026]
[0027] In some embodiments, the preparation steps of the hindered phenol antioxidant are:
[0028] Bisphenol A, 4-vinylphenylacetic acid and dichloromethane are uniformly mixed, solid phosgene-dichloromethane solution and triethylamine-dichloromethane solution are added dropwise thereto, and after the addition is completed, the system is heated to 150-160°C, aged, cooled to room temperature, filtered, and dichloromethane in the filtrate is removed to obtain a hindered phenol antioxidant.
[0029] In some embodiments, the molar ratio of bisphenol A to 4-vinylphenylacetic acid is 1:(1-1.3).
[0030] Preferably, the molar ratio of bisphenol A to 4-vinylphenylacetic acid is 1:1.2.
[0031] In some embodiments, the molar ratio of bisphenol A, solid phosgene and triethylamine is 1:(0.35-0.45):(1.2-1.4).
[0032] Preferably, the molar ratio of bisphenol A, solid phosgene and triethylamine is 1:0.04:1.3.
[0033] In the present invention, bisphenol A and 4-vinylphenylacetic acid are used as raw materials to synthesize a hindered phenol antioxidant, which belongs to an aromatic compound. The energy required for its excitation or ionization is lower than the bond energy of the polyethylene molecular chain, and it is easier to combine with electrons. The hindered phenol antioxidant can capture hot electrons in polyethylene, increase the trap density of polyethylene insulating materials, inhibit the injection of space charges, thereby reducing the energy of electrons, reducing the impact of electrons on polyethylene molecular chains, and improving the influence of the electrical free radical scavenger of polymer insulation on the space charge distribution during the polyethylene aging process. In addition, the hindered phenol antioxidant can capture macromolecular free radicals and small molecular products generated during the electrical aging process, improve the interface between the polyethylene crystal region and the amorphous region, thereby reducing the traps that cause the space charge to reside, reducing the generation of space charges, and can well inhibit the electrical aging of polyethylene materials.
[0034] The second aspect of the present invention provides a peroxide cross-linked polyethylene insulation material prepared by the preparation method described above.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The cross-linked polyethylene cable insulation material prepared in the present invention has excellent performance and high DC breakdown strength.
[0037] 2. The present invention uses a mercaptosilane coupling agent and a hindered phenol antioxidant to modify nano-silica, and applies the modified nano-silica to polyethylene insulating materials, which can significantly improve the dispersibility of the nano-silica and thus improve the DC breakdown strength of the polyethylene insulating materials.
[0038] 3. In the present invention, bisphenol A and 4-vinylphenylacetic acid are used as raw materials to synthesize a hindered phenol antioxidant, which can increase the trap density of polyethylene insulation materials, inhibit space charge injection, reduce the energy of electrons, reduce their impact on polyethylene molecular chains, and improve the electrical resistance of polyethylene insulation. The free radical scavenger has an effect on the space charge distribution during the aging process of polyethylene, and can inhibit the electrical aging of polyethylene materials. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0040] In order to better illustrate the specific implementation mode of the present invention, further examples are given below.
[0041] The low-density polyethylene base material used in the present invention is a low-density polyethylene base material with a brand name of DJ210 purchased from Sinopec Beijing Yanshan Branch (the melt flow rate is 2.1 g / 10 min according to GB / T 3682 standard test); the nano silicon dioxide used (average particle size is 50 nm) is purchased from Bohuasi Nano Technology (Ningbo) Co., Ltd.; the initiator used is azobisisobutyronitrile; and the mercaptosilane coupling agent used is γ-mercaptopropyltriethoxysilane.
[0042] Preparation Example 1
[0043] Preparation of hindered phenol antioxidants:
[0044] 0.1 mol of bisphenol A, 0.12 mol of 4-vinylphenylacetic acid and 500 mL of dichloromethane were uniformly mixed, and 5 mL of solid phosgene-dichloromethane solution (containing 0.04 mol of solid phosgene) and 5 mL of triethylamine-dichloromethane solution (containing 0.13 mol of triethylamine) were added dropwise thereto. After the addition was completed, the system was heated to 155° C., aged for 5 h, cooled to room temperature, centrifuged, filtered, and distilled to remove dichloromethane in the filtrate to obtain a hindered phenol antioxidant.
[0045] Preparation Example 2
[0046] The preparation steps of hindered phenol antioxidant modified silica are:
[0047] S1: 10 g of nano-silica was placed in 100 mL of anhydrous ethanol, 0.35 g of mercaptosilane coupling agent was added thereto, and after ultrasonic dispersion, the mixture was reacted in a closed environment at 115°C for 5 h, washed with deionized water for 3 times, vacuum dried, and then ground to obtain modified silica;
[0048] S2: In a nitrogen atmosphere, 6.5 g of the modified silica prepared in step (1) was mixed with 1 g of a hindered phenol antioxidant, 0.01 g of a photoinitiator TPO, and 10 mL of dichloromethane. The mixture was irradiated with an ultraviolet lamp having a wavelength of 365 nm at 0°C and 750 rpm / min for 1.5 h, and then vacuumed to obtain hindered phenol antioxidant modified silica.
[0049] The hindered phenol antioxidant used was obtained from Preparation Example 1.
[0050] Preparation Example 3
[0051] The preparation steps of hindered phenol antioxidant modified silica are:
[0052] S1: 10 g of nano-silica was placed in 100 mL of anhydrous ethanol, 0.7 g of mercaptosilane coupling agent was added thereto, and after ultrasonic dispersion, the mixture was reacted in a closed environment at 115°C for 5 h, washed with deionized water for 3 times, vacuum dried, and then ground to obtain modified silica;
[0053] S2: In a nitrogen atmosphere, 6.5 g of the modified silica prepared in step (1) was mixed with 1 g of a hindered phenol antioxidant, 0.01 g of a photoinitiator TPO, and 10 mL of dichloromethane. The mixture was irradiated with an ultraviolet lamp having a wavelength of 365 nm at 0°C and 750 rpm / min for 1.5 h, and then vacuumed to obtain hindered phenol antioxidant modified silica.
[0054] The hindered phenol antioxidant used was obtained from Preparation Example 1.
[0055] Preparation Example 4
[0056] The preparation steps of hindered phenol antioxidant modified silica are:
[0057] In a nitrogen atmosphere, 6.5 g of nano-silica was mixed with 1 g of hindered phenol antioxidant, 0.01 g of photoinitiator TPO, and 10 mL of dichloromethane. The mixture was irradiated with an ultraviolet lamp with a wavelength of 365 nm at 0°C and 750 rpm / min for 1.5 h, and then vacuumed to obtain hindered phenol antioxidant modified silica.
[0058] The hindered phenol antioxidant used was obtained from Preparation Example 1.
[0059] Preparation Example 5
[0060] The preparation steps of hindered phenol antioxidant modified silica are:
[0061] S1: 10 g of nano-silica was placed in 100 mL of anhydrous ethanol, 0.7 g of mercaptosilane coupling agent was added thereto, and after ultrasonic dispersion, the mixture was reacted in a closed environment at 115°C for 5 h, washed with deionized water for 3 times, vacuum dried, and then ground to obtain modified silica;
[0062] S2: In a nitrogen atmosphere, 6.5 g of the modified silica prepared in step (1) was mixed with 1 g of a hindered phenol antioxidant, 0.01 g of a photoinitiator TPO, and 10 mL of dichloromethane. The mixture was irradiated with an ultraviolet lamp having a wavelength of 365 nm at 0°C and 750 rpm / min for 1.5 h, and then vacuumed to obtain hindered phenol antioxidant modified silica.
[0063] The hindered phenol antioxidant used is commercially available 4,4'-thiobis(6-tert-butyl-m-cresol) (6-tert-butyl-m-cresol) (AO300).
[0064] Preparation Example 6
[0065] The preparation steps of modified silica are:
[0066] 10 g of nano-silica was placed in 100 mL of anhydrous ethanol, to which 0.7 g of mercaptosilane coupling agent was added, and after ultrasonic dispersion, the mixture was reacted in a closed environment at 115° C. for 5 h, washed with deionized water three times, vacuum dried, and ground to obtain modified silica.
[0067] Example 1
[0068] A method for preparing a peroxide cross-linked polyethylene insulation material for a 500kV ultra-high voltage DC cable comprises the following preparation steps:
[0069] 1 kg of low-density polyethylene base material was added into a reciprocating mixer for preliminary melting, 5 g of hindered phenol antioxidant modified silica was added and mixed evenly, and finally 40 g of diisopropylbenzene peroxide was added and kept warm at 70°C for 12 hours to obtain peroxide cross-linked polyethylene insulation material.
[0070] The hindered phenol antioxidant modified silica used is obtained from Preparation Example 2.
[0071] Example 2
[0072] A method for preparing a peroxide cross-linked polyethylene insulation material for a 500kV ultra-high voltage DC cable comprises the following preparation steps:
[0073] 1 kg of low-density polyethylene base material was added into a reciprocating mixer for preliminary melting, 25 g of hindered phenol antioxidant modified silica was added and mixed evenly, and finally 40 g of diisopropylbenzene peroxide was added and kept warm at 110°C for 11 hours to obtain peroxide cross-linked polyethylene insulation material.
[0074] The hindered phenol antioxidant modified silica used is obtained from Preparation Example 2.
[0075] Example 3
[0076] A method for preparing a peroxide cross-linked polyethylene insulation material for a 500kV ultra-high voltage DC cable comprises the following preparation steps:
[0077] 1 kg of low-density polyethylene base material was added into a reciprocating mixer for preliminary melting, 15 g of hindered phenol antioxidant modified silica was added and mixed evenly, and finally 40 g of diisopropylbenzene peroxide was added and absorbed at 80°C for 10 hours to obtain peroxide cross-linked polyethylene insulation material.
[0078] The hindered phenol antioxidant modified silica used is obtained from Preparation Example 2.
[0079] Example 4
[0080] The method for preparing peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable has the same specific implementation as Example 3, except that the hindered phenol antioxidant modified silica used is obtained from Preparation Example 3.
[0081] Example 5
[0082] The preparation method of peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable is the same as that of Example 3, except that the hindered phenol antioxidant modified silica used is obtained from Preparation Example 4.
[0083] Example 6
[0084] The preparation method of peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable is the same as that of Example 3, except that the hindered phenol antioxidant modified silica used is obtained from Preparation Example 5.
[0085] Comparative Example 1
[0086] The preparation method of peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable is the same as that of Example 3, except that the modified silica obtained in Preparation Example 6 of the same mass is used instead of the hindered phenol antioxidant modified silica.
[0087] Comparative Example 2
[0088] The preparation method of peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable is the same as that of Example 3, except that unmodified nano-silica of equal mass is used instead of hindered phenol antioxidant modified silica.
[0089] Comparative Example 3
[0090] The preparation method of peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable is the same as that of Example 3, except that the hindered phenol antioxidant obtained in Preparation Example 1 of the same mass is used instead of hindered phenol antioxidant modified silica.
[0091] Comparative Example 4
[0092] The preparation method of peroxide cross-linked polyethylene insulation material for 500kV ultra-high voltage DC cable is the same as that of Example 3, except that hindered phenol antioxidant and modified silica of equal mass are used instead of hindered phenol antioxidant modified silica.
[0093] The mass ratio of the hindered phenol antioxidant to the modified silica is 6.5:1. The hindered phenol antioxidant used is obtained from Preparation Example 1, and the modified silica is obtained from Preparation Example 6.
[0094] Performance test of peroxide cross-linked polyethylene insulation material
[0095] The test was conducted with reference to GB / T 1408.1-2016 Test Method for Electrical Strength of Insulating Materials: the peroxide cross-linked polyethylene insulating material obtained in the embodiment and the comparative example was placed in a flat vulcanizer, hot pressed for 20 min at 140°C and 10 MPa to complete the cross-linking process, and a circular sample with a thickness of 100 μm and a diameter of 100 mm was prepared. Five parallel samples were set for each embodiment or comparative example, and a cylindrical electrode structure was adopted. The diameter of the high-voltage electrode was 25 mm, the diameter of the grounding electrode was 50 mm, and the edges of the two electrodes had a 5 mm fillet. During the test, the sample and the electrode were immersed in a silicone oil liquid that met the requirements. When conducting the temperature change test, the oil tank containing the electrode was placed in a constant temperature oil bath and heated for 3 h to stabilize the temperature of the silicone oil and the electrode. The voltage was increased at a voltage increase rate of 0.3 kV / s until the sample was broken down, the breakdown voltage was read, and the corresponding DC breakdown field strength was calculated according to the formula E=U / d. The two-parameter Weibull distribution function is used to calculate the breakdown field strength, and the breakdown strength corresponding to the failure probability of 63.2% is used as the characteristic breakdown field strength of peroxide cross-linked polyethylene insulation material. The temperatures selected for the breakdown test are 20℃, 70℃ and 90℃ respectively.
[0096] The specific test results of the peroxide cross-linked polyethylene insulation materials in each embodiment are shown in Table 1, and the specific test results of the peroxide cross-linked polyethylene insulation materials in each comparative example are shown in Table 2.
[0097] Table 1
[0098]
[0099] Table 2
[0100]
[0101] It can be seen from Table 1 that the peroxide cross-linked polyethylene insulation materials prepared in the examples have better performance than the peroxide cross-linked polyethylene insulation materials in the comparative examples, and the peroxide cross-linked polyethylene insulation materials prepared in Examples 1-3 have the best DC breakdown strength at 20°C, 70°C and 90°C.
[0102] Compared with Example 3, in the preparation process of the hindered phenol antioxidant modified silica used in Example 4, the amount of mercaptosilane coupling agent used is too much, which weakens the "bond bridge" effect of the silane coupling agent, thereby reducing the performance of the peroxide cross-linked polyethylene insulation material; in the preparation process of the hindered phenol antioxidant modified silica used in Example 5, the mercaptosilane coupling agent is not used to modify the silica, and the nano silica cannot chemically react with the vinyl group in the hindered phenol antioxidant, which also reduces the performance of the peroxide cross-linked polyethylene insulation material; in the preparation process of the hindered phenol antioxidant modified silica used in Example 6, commercially available 4,4'-thiobis(6-tert-butyl-m-cresol) (6-tert-butyl-m-cresol) is used instead of the hindered phenol antioxidant synthesized in the present invention, which has no vinyl group and cannot react with the modified silica, thereby reducing the DC breakdown strength of the peroxide cross-linked polyethylene insulation material.
[0103] Compared with Example 3, in Comparative Example 2, an equal mass of unmodified nano-silica is used to replace the hindered phenol antioxidant modified silica, and the nano-silica is prone to agglomeration, which significantly reduces the performance of the peroxide cross-linked polyethylene insulation material; in Comparative Example 1, the modified silica obtained in Preparation Example 6 is used to replace the hindered phenol antioxidant modified silica, in Comparative Example 3, an equal mass of the hindered phenol antioxidant obtained in Preparation Example 1 is used to replace the hindered phenol antioxidant modified silica, and in Comparative Example 4, an equal mass of hindered phenol antioxidant and modified silica are used to replace the hindered phenol antioxidant modified silica. The modified silica and the hindered phenol antioxidant cannot produce a chemical reaction and have no synergistic effect, resulting in a decrease in the DC breakdown strength of the peroxide cross-linked polyethylene insulation material to varying degrees.
[0104] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
A method for preparing peroxide cross-linked polyethylene insulation material for 1.500kV ultra-high voltage DC cable, characterized in that: The method comprises the following preparation steps: The low-density polyethylene base material is added into a reciprocating mixer for preliminary melting, the hindered phenol antioxidant modified silica is added for uniform mixing, and finally dicumyl peroxide is added for heat preservation and absorption at 70-110°C for 10-12h to obtain peroxide cross-linked polyethylene insulation material.
2. The preparation method according to claim 1, characterized in that: The amount of the hindered phenol antioxidant modified silica is 0.5-2.5wt‰ of the low-density polyethylene base material.
3. The preparation method according to claim 1, characterized in that: The preparation steps of the hindered phenol antioxidant modified silica are: S1: putting nano-silica into anhydrous ethanol, adding mercaptosilane coupling agent thereto, and after ultrasonic dispersion, reacting in a closed environment at 110-120° C. for 4-6 hours, washing, vacuum drying and grinding to obtain modified silica; S2: In a nitrogen atmosphere, the modified silica of step (1) is mixed with a hindered phenol antioxidant, a photoinitiator TPO, and dichloromethane, and reacted with ultraviolet light for 1-2 hours at 0-4° C. with stirring, and then vacuumed to obtain hindered phenol antioxidant modified silica.
4. The preparation method according to claim 3, characterized in that: The average particle size of the nano silicon dioxide is 50-100 nm.
5. The preparation method according to claim 3, characterized in that: The amount of the mercaptosilane coupling agent is 2-6wt% of the nano silicon dioxide; the mercaptosilane coupling agent is gamma-mercaptopropyltrimethoxysilane or gamma-mercaptopropyltriethoxysilane.
6. The preparation method according to claim 3, characterized in that: The mass ratio of the modified silica to the hindered phenol antioxidant is (1-10):
1.
7. The preparation method according to claim 3, characterized in that: The structural formula of the hindered phenol antioxidant is: 。 8. The preparation method according to claim 7, characterized in that: The preparation steps of the hindered phenol antioxidant are: Bisphenol A, 4-vinylphenylacetic acid and dichloromethane are uniformly mixed, solid phosgene-dichloromethane solution and triethylamine-dichloromethane solution are added dropwise thereto, and after the addition is completed, the system is heated to 150-160°C, aged, cooled to room temperature, filtered, and dichloromethane in the filtrate is removed to obtain a hindered phenol antioxidant.
9. The preparation method according to claim 8, characterized in that: The molar ratio of bisphenol A to 4-vinylphenylacetic acid is 1:(1-1.3).
10. A peroxide cross-linked polyethylene insulation material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Crosslinked polyethylene cable insulating material and preparation method thereof
CN110791003A
Cited By
Polyethylene insulation material for ultrahigh-voltage cable and preparation method of polyethylene insulation material
CN119529411A